2007
DOI: 10.1177/0272989x06297391
|View full text |Cite
|
Sign up to set email alerts
|

Patients Derogate Physicians Who Use a Computer-Assisted Diagnostic Aid

Abstract: Patients may surmise that a physician who uses a DSS is not as capable as a physician who makes the diagnosis with no assistance from a DSS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
81
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(100 citation statements)
references
References 38 publications
10
81
4
Order By: Relevance
“…This study replicated the previous finding that physicians who use computer based diagnostic aids are rated less favorably across several variables than physicians who make an unaided diagnosis [7]. This research demonstrates that it is not the consultation of an outside source that patients find objectionable.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This study replicated the previous finding that physicians who use computer based diagnostic aids are rated less favorably across several variables than physicians who make an unaided diagnosis [7]. This research demonstrates that it is not the consultation of an outside source that patients find objectionable.…”
Section: Discussionsupporting
confidence: 83%
“…Physicians believe that to use such aids is to employ "cookbook" medicine, and undermine years of schooling and training. Patients give lower ratings of diagnostic ability, professionalism, and overall satisfaction to physicians using a computer-based aid during diagnosis [7].…”
Section: Introductionmentioning
confidence: 99%
“…When a causal schema includes multiple sufficient causes, the discounting principle suggests that the presence of facilitative external factors (e.g., standardized practices) reduces the extent to which people attribute an outcome to internal factors (e.g., human judgment; Himmelfarb & Anderson, 1975;Kelley & Michela, 1980). Research examining the use of standardized decision-making practices in the fields of medicine and accounting supports the tenets of attribution theory's discounting principle (Arkes, Shaffer, & Medow, 2007;Lowe, Reckers, & Whitecotton, 2002). Pezzo and Pezzo (2006), for example, found that a physician who made a proper diagnosis using intuition was generally credited with a having made a higher quality decision than a physician who arrived at the same diagnosis using a standardized approach.…”
Section: Personnel Assessment and Decisionsmentioning
confidence: 96%
“…Factors relating to this underutilization are commonly classified as pertaining to the clinical problem, patient factors, provider traits, system characteristics and the health-care environment 9 . We have been exploring issues affecting the psychological perspective of the provider on the use of decision aids 10,11 . Perhaps physicians simply do not put as much credence in the recommendation of a decision aid compared with the advice of a colleague.…”
mentioning
confidence: 99%